Diagnostic utility of fluorodeoxyglucose positron emission tomography in prosthetic joint infection based on MSIS criteria. (August 2019) - Kiran, M.; Donnelly, T D.; Armstrong, C.; Kapoor, B.; Kumar, G.; Peter, V.
Abstract : Aims: Prosthetic joint infection (PJI) and aseptic loosening in total hip arthroplasty (THA) can present with pain and osteolysis. The Musculoskeletal Infection Society (MSIS) has provided criteria for the diagnosis of PJI. The aim of our study was to analyze the utility of F18-fluorodeoxyglucose (FDG) positron emission tomography (PET) CT scan in the preoperative diagnosis of septic loosening in THA, based on the current MSIS definition of prosthetic joint infection. Patients and Methods: A total of 130 painful unilateral cemented THAs with a mean follow-up of 5.17 years (sd 1.12) were included in this prospective study. The mean patient age was 67.5 years (sd 4.85). Preoperative evaluation with inflammatory markers, aspiration, and an F18 FDG PET scan were performed. Diagnostic utility tests were also performed, based on the MSIS criteria for PJI and three samples positive on culture alone. Results: The mean erythrocyte sedimentation rate, C-reactive protein, and white cell count were 47.83 mm/hr, 25.21 mg/l, and 11.05 × 10 9 /l, respectively. The sensitivity, specificity, accuracy, negative predictive value, and false-positive rate of FDG PET compared with MSIS criteria were 94.87%, 38.46 %, 56.38%, 94.59 %, and 60.21%, respectively. The false-positive rate of FDG PET compared with culture alone was 77.4%. Conclusion: FDG PET has a definitive role in the preoperative evaluation of suspected PJI. This the first study to evaluate its utility based on MSIS criteria and compare it with microbiology results alone. However, FDG PET has a high false-positive rate. Therefore, we suggest that F18 FDG PET is useful in confirming the absence of infection, but if positive, may not be confirmatory of PJI. Cite this article: Bone Joint J 2019;101-B:910–914.